Utilizing Digital Technology in Islamic Religious Education to Enhance Student Participation: Evidence from an Indonesian Elementary School - Hamran Hamran; Mahsyar Idris; Andi Fitriani Djollong,; Djamaluddin Djamaluddin; Amir Patintingan (CV. Gerasi Insan Nusantara, 2026)
The integration of digital technology has become increasingly important in promoting student engagement and improving learning outcomes in Islamic Religious Education (IRE). This study aimed to examine the utilization of digital technology in IRE learning, explore its contribution to students’ active participation, and identify supporting and inhibiting factors influencing its implementation at SDN 74 Bolang, Enrekang Regency, Indonesia. A qualitative case study approach was employed involving 12 participants consisting of one principal, six classroom teachers, one Islamic Religious Education teacher, and four parents. Data were collected over a three-month period through observations, semi-structured interviews, and documentation. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings revealed that digital technologies such as Smart TVs, Corombut, digital Qur’an applications, instructional videos, Google Classroom, and other e-learning platforms significantly increased students’ participation, motivation, interaction, and understanding of Islamic Religious Education materials. Supporting factors included teacher commitment, technological availability, and administrative support, whereas inhibiting factors consisted of limited infrastructure, unequal access to devices, internet connectivity issues, and varying levels of digital literacy. The study concludes that digital technology creates more engaging, interactive, and student-centered learning environments. Practically, the findings provide guidance for schools and policymakers in designing effective technology-based Islamic Religious Education programs that foster active student participation and meaningful learning experiences.